Prevalence of Foot Drop in Lumbar Degenerative Disease - Nausheen Sajid Khan (International Journal of Allied Medical Sciences and Clinical Research, 2020)
The purpose of this study is to find out prevalence of foot drop in lumbar degenerative disease. 100 patients suffering from lumbar degenerative disease were included in the study between age group of 25-55 years from both genders. The medical research council scale was used, to evaluate the strength of tibialis anterior muscle by performing manual muscle test. Data was collected and Statistical Analysis was done by calculating its mean. In this study The Prevalence of Foot Drop in Lumbar Degenerative Disease was 8% and found out that most of the foot drop patient resulted from ignored cases of Lumbar Spinal Stenosis and Prolapse Intervertrebral Disc out of which most of them were males with farming occupation and most of them suffer unilaterally.